2014
DOI: 10.2147/opth.s56783
|View full text |Cite
|
Sign up to set email alerts
|

Blink patterns and lid-contact times in dry-eye and normal subjects

Abstract: PurposeTo classify blinks in dry eye and normal subjects into six subtypes, and to define the blink rate and duration within each type of blink, as well as the total lid-contact time/minute.Materials and methodsThis was a single-centered, prospective, double-blind study of eleven dry-eye and ten normal subjects. Predefined subjects watched a video while blinks were recorded for 10 minutes. Partial blinks were classified by percentage closure of maximal palpebral fissure opening: 25%, 50%, 75%. Complete blinks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…Dry eye patients spend more time with their eyes closed than normal patients. 20 Blink rate was significantly related to the OSDI scores of the subjects. The correlation coefficient meant that as the blink rate scores increased the OSDI scores of the participants also decreased.…”
Section: Discussionmentioning
confidence: 88%
“…Dry eye patients spend more time with their eyes closed than normal patients. 20 Blink rate was significantly related to the OSDI scores of the subjects. The correlation coefficient meant that as the blink rate scores increased the OSDI scores of the participants also decreased.…”
Section: Discussionmentioning
confidence: 88%
“…One explanation may be that eyes which have a thick tear lipid layer may have less of an urge to blink completely, and those with a thinner tear lipid layer are more inclined to blink completely in order to increase or restore tear lipid layer thickness. Ousler, et al reported that there were slightly more partial blinks (52.9%) among normal eyes than among dry eyes (50.96%) and that total contact time (lid-to-lid) was seven times longer in dry-eye subjects than normal subjects (0.565 versus 0.080 seconds, respectively; P<0.001)[ 42 ]. While poor tear film can be the result of partial blinking tendencies in those individuals [ 43 46 ], we might consider that another group of individuals exist who are less inclined to blink completely due to the presence of a robust tear film.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mostly focused on the spontaneous blink rate and the incomplete blink rate, but more complex patterns of blinks appeared in DED patients and each phase of the blink procedure might be important to understand the relationship between DED and blinking. The study from Ousler et al 18 indicated that extended lid closures and increased blink rates were the main differences between DED and healthy subjects. Rahman et al 19 found that rapid blinking was associated with worse ocular surface and tear film instability.…”
Section: Discussionmentioning
confidence: 98%